2016
DOI: 10.1039/c6ra24186g
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency hydrogen evolution reaction catalyzed by iron phosphide nanocrystals

Abstract: Iron phosphide ultrafine nanocrystals supported on carbon black were synthesized via a facile method and used as a highly efficient hydrogen evolution reaction electrocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…As shown in Fig. 4b [49][50][51] In addition to catalytic activity, stability is another critical factor to evaluate a good electrocatalyst, we investigated the stability of Co-FeS 2 /CoS 2 heterostructures via 1000 cycles scanning. As shown in Fig.…”
Section: -25mentioning
confidence: 99%
“…As shown in Fig. 4b [49][50][51] In addition to catalytic activity, stability is another critical factor to evaluate a good electrocatalyst, we investigated the stability of Co-FeS 2 /CoS 2 heterostructures via 1000 cycles scanning. As shown in Fig.…”
Section: -25mentioning
confidence: 99%
“…It can be found that all diffraction peaks in the XRD pattern are assigned to the FeP phase (JCPDS no. 65‐2565), confirming successful conversion of Fe‐based glycolate to FeP after the phosphidation reaction . The surface composition of the FeP hollow microspheres is investigated through XPS analysis (Figure b‐6d).…”
Section: Resultsmentioning
confidence: 77%
“…The Nyquist plots of the samples (Figure 6f) reveal a much higher charge-transfer resistance for CoMoP than for CoMoP 2 , which is consistent with the slower HER kinetics observed for the former electrocatalyst. [39] The lower carbon content of CoMoP and slightly larger particle size can account for the higher resistance of CoMoP. [39] To clarify the effect of the resistance on the relative performance of the catalysts, electrodes were additionally prepared by adding conductive carbon to the metal phosphide materials (these electrodes are named CoMoP-C and CoMoP 2 -C).…”
Section: Resultsmentioning
confidence: 99%